New twist on the regulation of NKG2D ligand expression - Cerwenka, Adelheid (The Rockefeller University Press, 2009)
The NK cell–activating receptor NKG2D plays a prominent role in antitumor immune responses. Expression of the multiple NKG2D ligands must be tightly controlled to guarantee that NK cells attack tumors but not healthy cells. New data reveal a novel mechanism of posttranslational regulation of the mouse NKG2D ligand MULT1, in which MULT1 is ubiquitinated and degraded in healthy cells. In response to UV stress or heat shock, ubiquitination of MULT1 decreases and cell surface expression increases. Thus, targeting the ubiquitination machinery in cancer cells might increase the susceptibility of tumors to NK cell–mediated killing.